Identity-Driven Cooperation versus Competition - Snower, Dennis J.; Bosworth, Steven J. (American Economic Review, 2016)
This paper seeks to extend the domain of identity economics by exploring motivational foundations of in-group cooperation and out-group competition. On this basis, we explore the reflexive interaction between individual economic decisions and social identities in response to technological change in market economies. Our analysis explores how technological change falling on marketable goods and services, rather than non-market caring relationships, leads to a restructuring of identities, which increases the scope of individualism and promotes positional competition at the expense of caring activities. Since positional competition generates negative externalities while caring activities create positive ones, these developments have important welfare implications.